Helper Innate Lymphoid Cells in Human Tumors: A Double-Edged Sword? - Tumino, Nicola; Vacca, Paola; Quatrini, Linda; Munari, Enrico; Moretta, Francesca; Pelosi, Andrea; Mariotti, Francesca Romana; Moretta, Lorenzo (Frontiers in Immunology, 2020)
Innate lymphoid cells (ILCs) were found to be developmentally related to Natural Killer (NK) cells. In humans, they are mostly located in “barrier” tissues where they contribute to innate defenses against different pathogens. ILCs are heterogeneous and characterized by a high degree of plasticity. ILC1s are Tbet+, produce IFN- and TNF-, but, unlike NK cells, are non-cytolytic and are Eomes-independent. ILC2 (GATA-3) secrete type-2 cytokines, while ILC3s secrete IL-22, IL-17. The cytokine signatures of ILC subsets mirror those of corresponding helper T-cell subsets. The ILC role in defenses against pathogens is well documented, while their involvement in tumor defenses is still controversial. Different ILCs have been detected in tumors. In general, the conflicting data reported in different tumors on the role of ILC, may reflect the heterogeneity and/or differences in tumor microenvironment (TM). The remarkable plasticity of ILCs suggests new therapeutic approaches to induce differentiation/switch towards ILC subsets more favorable in tumor control.